Persona as Personal Branding of Stand-Up Comedian in Indonesia - Sihombing, Lambok Hermanto; Sarwindah, Anak Agung; Siauw, Glenity Marchella; Chaniago, Steven (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Stand-Up comedy is the new trend of Pop Culture. In Indonesia, the Stand-Up comedy trend has spread to all places, from the very west of Indonesia Island to the Papua. This research analyses the pop culture of stand-up comedy and the new creative industry in Indonesia, focusing on Raditya Dika, Ernest Prakasa, Cak Lontong, Dodit Mulyanto and Uus. Furthermore, this research explores the persona of each comic that represents their style of performance. This essay also aims to find out the difference in persona of Indonesian Stand-Up Comedy artists and how they come up with the persona. For the data, we choose YouTube platform to be analyzed. We analyze the presented materials, video’s thumbnails and the responses from the audiences. We use three theories during this research, which are Personal Branding Theory, Digital Media Theory, and Social Semiotics. The result shows that these comics are having different unique persona that sticks to themselves and make people recognize them.